Local area networks new technologies,emerging standards - Madron, Thomas William 1937- (John Wiley and Sons, 1988)
Covers the latest developments in LAN technology, particularly as they relate to management goals. New topics include the role and impact of LANs on small businesses, the efficacy of client/server technology on LANs' use in the workplace, the necessity of having a variety of servers on a single LAN, several difficulties encountered in switching from a host-based to a LAN system. Details the role of UNIX, OS/2 and Windows NT in LAN planning, giving readers a sense of what software options they should select to best tailor their LAN operating system to fit their existing investments in software. Also describes available hardware choices.